Fighting the Mau Mau the British Army and counter-insurgency in the Kenya Emergency - Bennett, Huw C. (Cambridge military histories., 2013)
This new study of Britain's counterinsurgency campaign in Kenya examines the difference between official and accepted methods of conquering insurgents.